2000
DOI: 10.1128/iai.68.6.3748-3753.2000
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Endotoxin Associated with Lipopolysaccharide Tolerance Protects Mice against Fungal Infection

Abstract: Lipopolysaccharide (LPS) pretreatment of mice resulted in a significantly enhanced survival after disseminated Cryptococcus neoformans infection. The survival was associated with reduced fungal burden in tissues. LPS-pretreated mice had lower levels of cytokines in blood, spleen, and lungs and higher levels in brain. Pentoxifylline abolished the beneficial effect of LPS pretreatment.Whether the induction of endotoxin tolerance leads to an enhanced sensitivity to infection remains a challenging question. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 25 publications
2
48
1
2
Order By: Relevance
“…However, that finding has not been confirmed, and some investigators have detected an increase in mortality (4,5). Comparing these studies is difficult because of the different models of tolerance, bacterial infection and fungal infection involved (4,5,14,15). However, as in our study, a preponderance of more recent reports have shown that LPS tolerance offers a protective effect in sepsis (4,5,14,15).…”
Section: Lps Tolerance Modelcontrasting
confidence: 52%
See 4 more Smart Citations
“…However, that finding has not been confirmed, and some investigators have detected an increase in mortality (4,5). Comparing these studies is difficult because of the different models of tolerance, bacterial infection and fungal infection involved (4,5,14,15). However, as in our study, a preponderance of more recent reports have shown that LPS tolerance offers a protective effect in sepsis (4,5,14,15).…”
Section: Lps Tolerance Modelcontrasting
confidence: 52%
“…Comparing these studies is difficult because of the different models of tolerance, bacterial infection and fungal infection involved (4,5,14,15). However, as in our study, a preponderance of more recent reports have shown that LPS tolerance offers a protective effect in sepsis (4,5,14,15). We believe that the LPS tolerance model is characterized by changes in the immune system, and that these changes help it remain correctly regulated during sepsis.…”
Section: Lps Tolerance Modelmentioning
confidence: 43%
See 3 more Smart Citations